Elaboración de un dossier de las memorias conmemorativas del reencuentro pangüense, del cantón Pangua, de la provincia de Cotopaxi, en el periodo 2016 - Álvarez Reyes, Jorge Isaac (2016)
In relation of the Meeting of Panguense Family, it carries a lot of the tradition and culture of the region, it expresses in people kidness and happiness with all the other people. They communicate how this festivity was 70 years ago. In relation of the festivity it is very religious, because on August 10 they celebrate de day of San Lorenzo, putting in this way to the mainly people of that party, that are chosen by the Priest in charge of the parish, he allows to share the interest that exist in all of the habitants in this time the procession that holy image, the same that goes in a parade and it was carrying by the people in shoulders and all the retinue that share the parade.